The Wright 3 - Balliett, Blue, 1955- (Scholastic Press, 2006)
In the midst of a series of unexplained accidents and mysterious coincidences, sixth-graders Calder, Petra, and Tommy lead their classmates in an attempt to keep Frank Lloyd Wright's famous Robie House from being demolished.